Covalent phytobilin adducts of GUN4 implicate a photoprotective mechanism in chlorophyll biosynthesis - Yan Wang; Chunhui Hou; Nathan C. Rockwell; Pawel Brzezowski; Weiqing Zhang; Xiahe Huang; Qiuling Fan; Yingchun Wang; Bernhard Grimm; J. Clark Lagarias; Deqiang Duanmu (Proceedings of the National Academy of Sciences, 2026)
In the green alga Chlamydomonas reinhardtii, loss of chlorophyll synthesis under light stress is associated with degradation of the porphyrin-binding H-subunit (CHLH1) of magnesium chelatase (MgCh). This degradation is exacerbated by the absence of GENOMES UNCOUPLED 4 protein (GUN4) or its phycocyanobilin (PCB) ligand. PCB is synthesized from heme via the action of heme oxygenase HMOX1 followed by a ferredoxin-dependent bilin reductase (FDBR), a ubiquitous enzyme family in oxyphototrophs. We show that C. reinhardtii cells lacking GUN4 and/or HMOX1 accumulate the MgCh substrate protoporphyrin IX (PPIX), a potent generator of singlet oxygen ( 1 O 2 ). CHLH1 is unstable in gun4 or hmox1 mutants, phenotypes that can be rescued by deletion of known cytosolic 1 O 2 response proteins SAK1 or SOR1. GUN4 Trp residues are oxidized in the presence of PPIX and near-ultraviolet light (nUV), and spectroscopic changes in GUN4 seen in the presence of PCB are ablated by PPIX and nUV. The combination of PPIX, PCB, and nUV result in formation of covalent GUN4–bilin adducts. Such adducts are formed both in vivo and in vitro and are also formed in GUN4 proteins from cyanobacteria and plants. In GUN4 variants, loss of adduct formation correlates with Chlamydomonas growth defects under light stress. We propose that phytobilin adduct formation provides a mechanism for detoxifying 1 O 2 and sustaining chlorophyll synthesis in the presence of light and oxygen, thereby explaining the ubiquity of FDBRs in eukaryotic algae.